(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The educational system of a country will normally be aproduct of a variety of factors that characterize the life of the people ofthat country. Different countries have different patterns of education, dependingon the social, religious, linguistic, cultural, political and economic factors.India is no exception as almost all these factors have had helped the shapingof the educational system in the subcontinent. This chapter attempts to analysethe predominant factors and the remarkable events that prompted the growth ofIndia’s national renaissance and their direct and indirect impact on India’sfield of education and how far they affected the soul and content ofeducational pattern in Kerala. Any study on Indian education will be incompleteunless it is accompanied by an attempt to examine and evaluate the educationalideas propounded by renowned reformers like Raja Ram Mohan Roy, Sri RamakrishnaParamahamsa, Swami Vivekananda, Annie Besant, Rabindranath Tagore, SriAurobindo Ghosh and Mahatma Gandhi. They all, in their own way, contributed inrousing the national consciousness in the minds of the Indians in thenineteenth and the twentieth centuries.